Centralized role-based access control (RBAC) framework for critical web applications - Goudarzi, Alireza (Tafford Publishing, 2008)
Development and enhancement of the web technologies have made them a reliable alternative for regular desktop applications, especially after the Web 2.0 wave. The only problem that IT managers still resist - and for good reason - is the high potential of security breaches in these applications. If web applications are going to replace desktop applications, there should be a solid security framework which can also work the same way desktop security mechanism work to make them completely ready for corporate and sensitive situations, that is using a flexible administrative role based access control. The current implementations to tackle this issue are based on enterprise development frameworks like J2EE or.NET. However popularity of opensource platforms in enterprise environment calls for open-source alternatives. This paper presents and implementation of a centralized role based access control using popular open-source products PHP and MySQL. © 2008 Atilla Elçi.
1st International Conference on Security of Information and Networks, SIN 2007 --
Keywords: Access control in enterprise open-source web application; Access control in web based systems; Authentication and access control in web applications; Centralized security in web systems; High security websites; PHP security framework; Role based access control; Secure web access; Sensitive web applications; Web security